USING INSTAGRAM REELS TO INCREASE SPEAKING SKILL IN PROMOTION OF TOURSIM BY YOUTH OF COMMUINTY (KARANG TARUNA) TELAGABIRU - Hamzah, Amir (Journal of Education, Linguistics, Literature and Language Teaching, 2024)
In Indonesia, many influencers use English to build their personal brand on social media such as Facebook or Instagram, and this condition is great opportunities to promote the wonderful Indonesia using social media such as Instagram Reels, and this condition was created in Tanjungbumi under - district, youth community (Karang Taruna)."Pantai Biru" is one of the rural areas and the tourist destination since 2019 has been the popular Pantai Biru located in Tanjungbumi Bangkalan East Java, it is located in the village of Telaga Biru, which also has great view, and there were many guests during the weekend, the tourism is managed by Pantai Biru Youth Community they always advertise but sometimes they used English to show international tourist but the problem is they don't speak English they speak just local language, this research is qualitative research and use : (1) observation, (2) interview, (3) questionnaire and (4) documentation as the instruments.The researcher began to investigate the promotion activities when the weekend at 14th July to 21st July 2024 and this activities was used the Instagram account, in this research use several research instruments such as observation checklist, interview, and questionnaire after that the data was put to the procedure.From this research the youth community can help increase the CEFR standard better than before (Common European Framework of Reference for Languages) by using Instagram reel and good to get international audience.